Frequência de higiene bucal na manutenção da saúde gengival - Pinto, Tatiana Militz Perrone (2012)
The objective of this randomized blind clinical trial was to evaluate, in individuals using the appropriate oral hygiene method, the frequency of plaque removal hygiene in the maintenance of gingival health. Eligible patients (maximum 15% of gingival bleeding) underwent a pre-experimental period in order to eliminate factors that could interfere with proper plaque control, and obtain gingival health (maximum 5% of gingival bleeding). Fifty-two patients were randomized into four groups according to the frequency of oral hygiene (every 12h, 24h, 48h or 72h). Plaque Index (PLI) and Gingival Index (GI) were evaluated by two trained and blinds examiners at baseline, 15 days and 30 days. The primary outcome was the increase of the mean GI, and the secondary outcomes was IPL changes, and mean percentage of sites with different GI scores throughout the experimental period. Three patients quit the study (one from the 12h group and two from the 48h group). Regarding the PLI, the 12h group showed no changes during the experimental period. The other groups showed a significant increase in the average PLI between baseline and 15 days, with the maintenance of average plaque levels at 30 days. In the 12h and 24h groups, no average GI alterations were observed. In the 48h and 72h groups, we observed an increase in the mean GI between baseline and 15 days, sustained at 30 days. When the same analysis was performed by categorizing the sites in free and proximal surfaces, the same model of plaque accumulation and inflammatory changes was observed. However, in the proximal surfaces, the GI and PLI mean were always higher than those observed in free surfaces. At the end of study, the mean percentage of sites presenting scores of 1 and 2 in the IG was significantly greater in the 48h and 72h groups compared to the 12h and 24h groups. We conclude that frequency of plaque removal of 12h and 24h are compatible with gingival health. Key-words: Gingivitis. Toothbrushing. Oral hygiene.